Efek Neurologis Hiperkalemia dan Hipokalemia - Jason Adiwardhana; Budi Riyanto Wreksoatmodjo (Cermin Dunia Kedokteran, 2023)
Electrolyte disorders may interfere with human bodily function. Potassium is the most dominant intracelullar ion; lack (hypokalemia) or excess (hyperkalemia) potassium might give rise to cardiovascular and neuromuscular symptoms. Management consist of potassium serum correction alongside frequent electrocardiography monitoring. Implications of hypokalemia and hyperkalemia should always be taken considered, especially in elderly populations. Central nervous system involvement is currently unknown.